DEVELOPMENT OF METHODS FOR THE IDENTIFICATION OF FLAVONOIDS AND PHENOLCARBONIC ACIDS IN THE MEDICINAL PLANT RAW MATERIALS OF CREEPING THYME - Зарівна, Надія (SWorldJournal, 2023)
The work presents the development of a methodology for the identification of flavonoids and phenolic acids in medicinal plant raw materials of creeping thyme. In the pharmacotherapy of the pathology of the upper respiratory tract, a significant proportion